Where civil blood made soldiers hands unclean; rethinking, war-time coercion in rural Rhodesia: reflections on the Chivi experience 1976-1980 - Mazarire, Gerald C. (2016)
The Rhodesian Security Forces and ZANLA guerrillas operating in Chivi had to win the war! It mattered little to them whether this goal was to be achieved by means fair or foal, and as the war progressed, the problem was aggravated by their ever increasing numbers in the battlefield. With more emphasis being placed on quantity rather than quality, in recruitment as well as training, the calibre of the forces on both sides of the battlefront deteriorated rapidly as well. This corresponded directly with the deterioration of relations between the combatants themselves and the civilian population at large.